EMPOWERING MARGINALIZED CHILDREN THROUGH COMMUNITY-BASED EDUCATION: EVIDENCE FROM GAJAHWONG SCHOOL IN LEDHOK TIMOHO, YOGYAKARTA - Aat, Aat; Riyadi, Agus; Karim, Abdul; Leengaedayee, Paisul (Jurnal Al-Ijtimaiyyah, 2026)
Marginalized children are a vulnerable group who often experience limited access to education, a decent learning environment, and social support. The involvement of Gajahwong School as a form of community empowerment is crucial for children's well-being. This study aims to analyze two aspects: First, this study analyzes the educational conditions of marginalized children in Ledhok Timoho Village before the presence of Gajahwong School. Second, this study analyzes the role of Gajahwong School in the empowerment process of marginalized children in Ledhok Timoho Village. Using qualitative methods with purposive sampling techniques. The research subjects included the principal, educators, parents/guardians of students, and students of Gajahwong School. Data were obtained through observation, interviews, and documentation. The findings show that before the presence of Gajahwong School, children in Ledhok Timoho Village generally faced various problems, such as low motivation to learn, limited access to education, lack of parental support, and a social environment that was less supportive of child development. Gajahwong School provides an alternative non-formal learning space that focuses on local curriculum-based education. Gajahwong School plays a role in raising awareness and the importance of education for marginalized children. With the involvement of educators, volunteers, families, and communities, education becomes more accessible and relevant to previously marginalized students. Although this study had limitations in gathering informants, it was able to demonstrate the conditions of marginalized children before and after the school's establishment. Therefore, this research goes beyond simply addressing the beneficiaries and strengthening the bottom-up approach to developing alternative education.